LIVING HADITH IN CONTEMPORARY ACEH: Spiritual Experience and Collective Identity in the Rateb Seuribe Tradition - Al-Musyarraf, Muhammad Syifa; Nurhadi, Nurhadi (RIWAYAH, 2026)
This study investigates the practice of prophetic traditions concerning dhikr within the Rateb Seuribe tradition in Aceh as an expression of living hadith, emphasizing how hadith are interpreted, embodied, and transmitted through lived religious practices rather than remaining merely textual doctrines. Using a qualitative phenomenological approach, data were gathered through in-depth interviews with five informants, participant observation, and textual analysis of relevant hadith, and subsequently analyzed to uncover the essential meanings of participants’ experiences. The findings indicate that Rateb Seuribe functions as both a spiritual and social medium. Spiritually, participants associate emotional tranquility, sincerity in worship, and a perceived closeness to God with prophetic teachings on gatherings of remembrance, while socially, the collective recitation promotes solidarity, egalitarian interaction, and communal cohesion that extend beyond ritual settings into everyday cooperation and religious engagement. These experiences demonstrate how scriptural narratives shape religious consciousness and collective identity. Accordingly, the study concludes that Rateb Seuribe represents an embodied form of living hadith, illustrating the dynamic interaction between prophetic tradition, local culture, and collective spirituality in contemporary Acehnese society. Academically, this research contributes to the growing field of living hadith studies by offering a phenomenological perspective on the experiential dimensions of dhikr practices and by highlighting how local ritual traditions serve as spaces where prophetic teachings are continuously negotiated, internalized, and reproduced within the socio-cultural context of Aceh. Penelitian ini mengkaji praktik tradisi kenabian mengenai dhikr dalam tradisi Rateb Seuribe di Aceh sebagai bentuk living hadith, dengan menekankan bagaimana hadis ditafsirkan, diwujudkan, dan ditransmisikan melalui praktik keagamaan yang dijalani, bukan sekadar sebagai doktrin tekstual. Dengan menggunakan pendekatan fenomenologi kualitatif, data dikumpulkan melalui wawancara mendalam terhadap lima informan, observasi partisipatif, dan analisis tekstual terhadap hadis-hadis yang relevan, kemudian dianalisis untuk mengungkap makna esensial dari pengalaman para partisipan. Temuan penelitian menunjukkan bahwa Rateb Seuribe berfungsi sebagai medium spiritual sekaligus sosial. Secara spiritual, para partisipan mengaitkan ketenangan batin, keikhlasan dalam beribadah, dan kedekatan yang dirasakan dengan Tuhan dengan ajaran Nabi tentang majelis zikir, sedangkan secara sosial, pembacaan dhikr secara kolektif mendorong solidaritas, interaksi yang egaliter, dan kohesi komunitas yang melampaui konteks ritual hingga tercermin dalam kerja sama sehari-hari dan keterlibatan keagamaan. Pengalaman-pengalaman tersebut menunjukkan bagaimana narasi-narasi skriptural membentuk kesadaran keagamaan dan identitas kolektif. Dengan demikian, penelitian ini menyimpulkan bahwa Rateb Seuribe merupakan bentuk perwujudan living hadith yang memperlihatkan interaksi dinamis antara tradisi kenabian, budaya lokal, dan spiritualitas kolektif dalam masyarakat Aceh kontemporer. Secara akademik, penelitian ini berkontribusi terhadap perkembangan kajian living hadis dengan menawarkan perspektif fenomenologis mengenai dimensi pengalaman dalam praktik dhikr serta menegaskan bahwa tradisi ritual lokal merupakan ruang di mana ajaran-ajaran Nabi terus dinegosiasikan, diinternalisasikan, dan direproduksi dalam konteks sosial-budaya masyarakat Aceh.